Tapered Fiber Coated with Hydroxyethyl Cellulose/Polyvinylidene Fluoride Composite for Relative Humidity Sensor - M. Z. Muhammad; A. Lokman; M. Batumalay; H. Arof; H. Ahmad; S. W. Harun (Advances in Materials Science and Engineering)
A simple relative humidity (RH) sensor is demonstrated using a tapered fiber coated with hydroxyethyl cellulose/polyvinylidene fluoride (HEC/PVDF) composite as a probe. This coating acts as an inner cladding whose refractive index decreases with the rise in humidity and thus allows more light to be transmitted in humid state. A difference of up to 0.89 dB of the transmitted optical power is observed when RH changes from 50% to 80% in case of the silica fiber probe. The proposed sensor has a sensitivity of about 0.0228 dB/%RH with a slope linearity of more than 99.91%. In case of the plastic optical fiber (POF) probe, the output voltage of the sensor increases linearly with a sensitivity of 0.0231 mV/%RH and a linearity of more than 99.65% as the relative humidity increases from 55% to 80%.